Lutheran churches in Africa: Vitality, challenges, and opportunities for the new face of Lutheranism in the 21st century. Issue 1 (10th December 2019) - Ng'weshemi, Andrea M.
Abstract: It is acknowledged and well documented that Christianity is rapidly changing from being the religion of Europe and North America to a religion of South America, Africa, and Asia. Of the three regions, Africa is experiencing the fastest Christian growth. This paper examines one of the many Christian denominations and movements that are participating in that growth in Africa, namely Lutheranism. Reasons behind the steady expansion, challenges faced, and the implications of the rise of Lutheranism in Africa will be highlighted.